OPTIMASI WAKTU FERMENTASI JAMUR SIMBION DARI SPONGE Rhabdastrella SP. DAN UJI AKTIVITAS ANTIBAKTERINYA - Mahfur Mahfur; Khafidz Mahbub; Nada Safira Salsabila; Maulida Nur Istiqomah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Sponges are known have many metabolites compounds and potential to be used as raw materials for medicines. spongesare have the ability to form symbiosis with microorganisms. Rhabdastrela sp is have to contain various secondary metabolites, especially the Triterpenes group. The fermentation process is a method to produce abundant secondary metabolite from microorganisms such as symbiont fungi. This study aims to determine the optimal fermentation time for the symbiont fungus Rhabdastrella sp. by looking at the secondary metabolites produced and their antibacterial activity. This research is included of experimental research. Cultivation of the sponge Rhabdastrella sp. for the growth of symbiont fungi. Followed by a fermentation process with variations in time with 2,4,6,8,10,12, and 14 days to get the secondary metabolites produced. Liquid liquid extraction was carried out to obtain secondary metabolites. The final stage is TLC profile and test the antibacterial activity of extract using the well-diffusion method. The results showed that the long fermentation time affected the secondary metabolites obtained, and their antibacterial activity. The profile of secondary metabolites showed that the 12th day of fermentation had the most complex secondary metabolites and the highest yield and had a clear zone of 12.5 ± 0.26 mm.